Exploring Children's Morality: Theory, Data, and Practice in Early Childhood Education Yogyakarta - Rosyida, Fatia; Syamsudin, Amir; Yusuf, Lisanun Thoyyibah (UPI Kampus Cibiru, 2025)
The moral development of early childhood is crucial for shaping their character and social interaction. This study examines the efficacy of the Project Approach in fostering moral development in young children within early childhood education settings. The study employed a mixed-methods approach, combining quantitative scoring of moral development with qualitative analysis of the children's responses. Using a five-point scoring rubric, the researchers assessed the moral reasoning abilities of the child participants through observations. The findings indicate that a majority of the children exhibit notable progress in their moral development, predominantly clustering within the